Pressure vessels field manual common operating problems and practical solutions - Stewart, Maurice (Gulf Professional Pub., 2012)
The majority of the cost-savings for any oil production facility is the prevention of failure in one of the production equipment such as pressure vessels. Money lost through lost production far outweighs expenses associated with maintenance and proper operation. However, many new engineers lack the necessary skills to effectively find and troubleshoot operating problems while experience engineers lack knowledge of the latest codes and standards. The fifth book in the Field Manual Series, the Pressure Vessel Operations Field Manual provides new and experienced engineers with the latest tools to alter, repair and re-rate pressure vessels using ASME, NBIC and API 510 codes and standards. Step-by-step procedure on how to design, perform in-shop and in-field inspections and repairs, perform alterations and re-rate a pressure vessel How to select the appropriate vessel specifications, evaluate associated reports and determine allowable stresses Calculations for stresses in pressure vessels Select the appropriate materials of construction for a pressure vessel Design pressure vessels using the ASME Code Section VIII, Division 1 and 2 to best fit the circumstance.
Keywords: ASME boiler & pressure vessel code.; Pressure vessels -- Maintenance and repair -- Handbooks, manuals, etc.; Pressure vessels -- Maintenance and repair -- Standards -- United States -- Handbooks, manuals, etc.; Pressure vessels -- Inspection -- Handbooks, manuals, etc.; Pressure vessels -- Inspection -- United States -- Handbooks, manuals, etc.; Boilers -- Maintenance and repair -- Handbooks, manuals, etc.; Boilers -- Maintenance and repair -- Standards -- United States -- Handbooks, manuals, etc.; Boilers -- Inspection -- Handbooks, manuals, etc.; Boilers -- Inspection -- United States -- Handbooks, manuals, etc.; elektronické knihy; electronic books